Unveiling Legal Scholarly Landscapes: A Comprehensive Analysis of Trends and Contributors in Contemporary Legal Academia - Melanie Merliya Cahyo; Rifqi Ridlo Phahlevy; Irta Fiddina (Proceedings of The ICECRS, 2023)
This data article presents a comprehensive analysis of scholarly works related to cyberlaw and online social networking. The goal was to identify the most prolific institutions and authors contributing to this field. Data was collected from scholarly works available on Lens.org, filtered for journal articles in the "law" category, and supplemented with image analysis. Results revealed that in 2017 and 2018, the highest number of publications were recorded. Notably, the article titled "Smart Contracts: Terminology, Technical Boundaries, and Real-World Complexity" garnered the most access. Eliza Mik, Fawzia Cassim, and Warren B Chik emerged as the most active authors, each contributing two documents. The University of South Africa emerged as the most active institution in the field of law. The top journal, "Potchefstroom Electronic Law Journal," was published by the Academy of Science of South Africa, while the Academy itself was the most prolific publisher. In the realm of online social networking, the leading institution was highlighted. These insights offer valuable knowledge for researchers and students interested in cyberlaw and online social networking.Highlights : Analysis of scholarly works in cyberlaw and online social networking. Identification of top institutions, authors, and publications in the field. Valuable insights for researchers and students in law and technology. Keywords: data analysis, cyberlaw, online social networking, scholarly works, institutional insights